2011
DOI: 10.1002/cncr.26107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐related mortality in children with acute lymphoblastic leukemia in Central America

Abstract: BACKGROUND:The objectives of this study were to describe the incidence, timing, and predictors of treatmentrelated mortality (TRM) among children with acute lymphoblastic leukemia (ALL) in El Salvador, Guatemala, and Honduras. METHODS: Patients aged <20 years who were diagnosed with ALL between January 2000 and March 2008, who received treatment in any of the 3 countries, and who started induction chemotherapy were included in the study. Almost all patients were treated on the El Salvador-Guatemala-Honduras II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 29 publications
6
66
1
8
Order By: Relevance
“…[2][3][4][5][6][7] As the largest contributor to TRM, infectious complications such as varicella have a greater impact on outcomes and costs of pediatric cancer in LMIC. [2][3][4][5][6][7] Varicella-zoster virus (VZV) infection causes significant morbidity and mortality in immunecompromised children, including those undergoing treatment for cancer. [9][10][11] Previous studies have reported the risk of disseminated infection in these patients, in the absence of prophylaxis or treatment with acyclovir, to be approximately 32%-50%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7] As the largest contributor to TRM, infectious complications such as varicella have a greater impact on outcomes and costs of pediatric cancer in LMIC. [2][3][4][5][6][7] Varicella-zoster virus (VZV) infection causes significant morbidity and mortality in immunecompromised children, including those undergoing treatment for cancer. [9][10][11] Previous studies have reported the risk of disseminated infection in these patients, in the absence of prophylaxis or treatment with acyclovir, to be approximately 32%-50%.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Compared with children in high-income countries (HIC), children in LMIC are disproportionately affected by treatment-related mortality (TRM), defined as death due to adverse effects of treatment rather than disease progression. [2][3][4][5][6][7][8] In children with acute lymphoblastic leukemia (ALL), TRM has been estimated to be in the range of 11-21% in LMIC, compared with 1-3% in HIC. [2][3][4][5][6][7] As the largest contributor to TRM, infectious complications such as varicella have a greater impact on outcomes and costs of pediatric cancer in LMIC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B12 deficiency has also been associated with disordered hematopoiesis and dysfunctional immune response leading to increased susceptibility to infections [11]. Most of the deaths seen in children from the developing countries undergoing treatment for ALL occur during the initial phases of treatment due to infections and intolerance to chemotherapy [12,13]. Studies investigating the nutritional factors behind this poor outcome are scarce.…”
mentioning
confidence: 99%
“…The possible risks were (a) children aged older than 10 years and (b) those with a CNS disease at diagnosis (Bajel et al, 2008;Silverman et al, 2011). Immunophenotype did not significantly affect the relapse-free rate as in other studies (Gupta et al, 2011). It may be that patients with high risk disease had a greater chance of disease recurrence; however, our risk stratification criteria were not strictly clarified since the molecular abnormalities of the host were not included.…”
Section: Discussionmentioning
confidence: 67%